The Pattern Of Internet Exposure And Its Impact Towards Understanding Islam Among Academicians In Ukm And Usim - Bin Borham, A; Bin Abd Ghani, Z (Natl Univ Malaysia, Fac Social Sciences & Humanities, 2024)
The internet has brought a new concept in communicating Islamic Da'wah. Through the internet, the process of learning and understanding of Islam becomes more convenient for Muslim and Non-Muslim throughout the word. However, due to the flooding of information on Islam through internet, it has caused some significant effect to certain groups who are over exposed to too much information, especially the academician. Thus, this research will attempt to examine the pattern of internet exposure and its impact towards the understanding of Islam among academician. For this purpose, 206 academicians from the National University of Malaysia (UKM) and Islamic Science University of Malaysia (USIM) were selected as respondents. Research showed that there is high exposure of internet among respondents based on the academician demography and internet usage. In the context of understanding of Islam, this research reveals that the internet has an average effect on the respondents with regards to the aspects of akidah and shari. ah issues. At the same time, there is significant effect brought by internet on the aspect of akhlak. Most respondents are optimistic towards the impact of websites and blogs that shared information related to Islam and religiosity. Research has also shown that flooding of Islamic information and online fatwas through internet has caused some effects among authoritative religious institute such as JAKIM and State Religious Departments. Nevertheless, the Internet has to be used cautiously and diligently as there are aspects which are able to bring about negative effects to the life of the Islamic society.